Supporting Fourth-Grade Students' Word Identification Using Application Software. Issue 4 (19th May 2017) - Moser, Gary P.; Morrison, Timothy G.; Wilcox, Brad
Abstract : A quasi-experimental study examined effects of a 10-week word structure intervention with fourth-grade students. During daily 10–15-minute practice periods, students worked individually with mobile apps focused on specific aspects of word identification. Pre- and post-treatment assessments showed no differences in rate and accuracy of oral reading between groups that did and did not use the apps, with little effect on motivation to read. Some differences were found in level of texts read and in spelling favoring the intervention students. However, practical significance was found in gains in percentile rank scores on standardized vocabulary and comprehension measures.